Biomaterials in Clinical Practice Advances in Clinical Research and Medical Devices (Springer International Publishing, 2018)
This book covers the properties of biomaterials that have found wide clinical applications, while also reviewing the state-of-the-art in the development towards future medical applications, starting with a brief introduction to the history of biomaterials used in hip arthroplasty. The book then reviews general types of biomaterials - polymers, ceramics, and metals, as well as different material structures such as porous materials and coatings and their applications - before exploring various current research trends, such as biodegradable and porous metals, shape memory alloys, bioactive biomaterials and coatings, and nanometals used in the diagnosis and therapy of cancer. In turn, the book discusses a range of methods and approaches used in connection with biomaterial properties and characterization - chemical properties, biocompatibility, in vivo behaviour characterisation, as well as genotoxicity and mutagenicity - an d reviews various diagnostic techniques: histopathological analysis, imagining techniques, and methods for physicochemical and spectroscopic characterization. Properties of stent deployment procedures in cardiovascular surgeries, from aspects of prediction, development and deployment of stent geometries are presented on the basis of novel modelling approaches. The last part of the book presents the clinical applications of biomaterials, together with case studies in dentistry, knee and hip prosthesis. Reflecting the efforts of a multidisciplinary team of authors, gathering chemical engineers, medical doctors, physicists and engineers, it presents a rich blend of perspectives on the application of biomaterials in clinical practice. The book will provide clinicians with an essential review of currently available solutions in specific medical areas, also incorporating non-medical solutions and standpoints, thus offering them a broader selection of materials and implantable solutions. This work is the result of joint efforts of various academic and research institutions participating in WIMB Tempus project, 543898-TEMPUS-1-2013-1-ES-TEMPUS-JPHES, "Development of Sustainable Interrelations between Education, Research and Innovation at WBC Universities in Nanotechnologies and Advanced Materials where Innovation Means Business", co-funded by the Tempus Programme of the European Union.